Concilios y legistación imperial - Bajo, Fe (Studia Historica. Historia Antigua, 2010)
RESUMEN: La colaboración instaurada a partir de Constantino entre la Iglesia y el poder político produjo toda una serie de interpretaciones que afectaron no sólo al plano de lo ideológico-religioso sino a las propias estructuras político-sociales del Imperio. Así se procedió a una reorganización del derecho sobre bases nuevas. La creación de la iurisdictio episcopalis, las exenciones fiscales a las propiedades eclesiásticas y a los propios clérigos o el monopolio concedido a la Iglesia de muchas de las antiguas instituciones civiles tales como el patronato ciudadano, dan cuenta de las interrelaciones entre la normativa jurídica imperial inserta en el Codex Theodosianus y las disposiciones conciliares. ABSTRACT: The cooperation between the Church and the Worldly Power started with Constantine resulted in a series of interpretations not only from the ideologicalreligious point of view, but also affecting the socio-political structures of the Empire. Thus, and on a new ground reorganisation of the laws was undertaken. The creation of a iurisdictio episcopalis, financial exemptions for ecclesiastic properties and for the clergy itself, or the monoply granted by the Church to many former civil institutions, such as the board of citizens, account for the interrelations between the imperial jurisdiction as described in the Codex Theodosianus and the Council dispositions.